2005
DOI: 10.1111/j.1365-2141.2005.05548.x
|View full text |Cite
|
Sign up to set email alerts
|

Interphase fluorescence in situ hybridization with an IGH probe is important in the evaluation of patients with a clinical diagnosis of chronic lymphocytic leukaemia

Abstract: Summary Translocations involving IGH are common in some lymphoid malignancies but are believed to be rare in chronic lymphocytic leukaemia (CLL). To study the clinical utility of fluorescence in situ hybridization (FISH) for IGH translocations, we reviewed 1032 patients with a presumptive diagnosis of CLL. Seventy‐six (7%) patients had IGH translocations. Pathology and clinical data were available for the 24 patients evaluated at the Mayo Clinic. Ten (42%) patients had IGH/cyclin D1 fusion and were diagnosed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
50
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 20 publications
6
50
0
2
Order By: Relevance
“…Similar to the patients we report, this patient had classic cytology and immunophenotype, and splenomegaly (Reddy et al, 2006). In other reports with smaller cohorts of CLL patients, either none or rare cases with MYC translocation have been identified by either conventional cytogenetic analysis or FISH studies (Rechavi et al, 1989;Raghoebier et al, 1991;Dohner et al, 2000;Nowakowski et al, 2005;Nelson et al, 2007).…”
Section: Discussionsupporting
confidence: 59%
“…Similar to the patients we report, this patient had classic cytology and immunophenotype, and splenomegaly (Reddy et al, 2006). In other reports with smaller cohorts of CLL patients, either none or rare cases with MYC translocation have been identified by either conventional cytogenetic analysis or FISH studies (Rechavi et al, 1989;Raghoebier et al, 1991;Dohner et al, 2000;Nowakowski et al, 2005;Nelson et al, 2007).…”
Section: Discussionsupporting
confidence: 59%
“…16 ). Translocations and deletions of 14q32 involving the IGH gene were found in up to 5% of CLL patients [17][18][19] . Other chromosomal abnormalities involving regions of 3q, 8q, 9p and other regions are less frequent in CLL.…”
Section: Introductionmentioning
confidence: 99%
“…This contrasts with earlier studies reporting a TFS of only 2 months in patients with 14q32/IGH translocations (n ¼ 18) 6 and a progression-free survival (PFS) of 20.6 months in patients with IGH/BCL2 translocations (n ¼ 8). 5 However, another study showed different PFS and time to treatment (TTT) according to the partner gene. Indeed, translocations involving BCL3 were correlated with a worse prognosis than those involving BCL2 with a median TTT of 1.5 and 3.6 years, respectively (P ¼ 0.017).…”
mentioning
confidence: 99%
“…[2][3][4] Their significance remains poorly understood. 5 In published series, 4,6 part of the cases have unknown partner genes. Recurrent partner genes include BCL2, BCL3, BCL11A and CMYC.…”
mentioning
confidence: 99%